Analisis Kelayakan Tekno-Ekonomi Menggunakan Metode Net Present Value (NPV) dan Internal Rate Of Return (IRR) pada Konversi Mesin Diesel 1-Silinder ke Biodiesel B20 Berbasis Limbah Minyak Jelantah pada Industri Tahu Skala UMKM - Rama Abimanyu (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
The reliance of the MSME-scale tofu industry on diesel fuel for single-cylinder diesel engines results in high operating costs and increased exhaust emissions. B20 biodiesel made from used cooking oil is a fuel alternative with the potential to reduce production costs, minimize waste, and support the adoption of renewable energy. This study aims to analyze the techno-economic feasibility of using B20 biodiesel derived from used cooking oil in single-cylinder diesel engines through a Systematic Literature Review (SLR) approach, adhering to the PRISMA principles. The reviewed literature consists of scientific publications from 2019 to 2025 that discuss the performance of diesel engines fueled by B20 biodiesel, the utilization of used cooking oil as a biodiesel feedstock, and technical-economic analyses using Net Present Value (NPV) and Internal Rate of Return (IRR). The results of the study indicate that the use of B20 biodiesel leads to a 1–3% decrease in effective power, a 2–5% decrease in thermal efficiency, and a 5–10% increase in specific fuel consumption. Nevertheless, these changes remain within the operational tolerance limits of SMEs and do not require significant engine modifications. From an environmental perspective, B20 biodiesel reduces CO, HC, and particulate emissions, although there is a tendency for NOx emissions to increase. From an economic perspective, a positive NPV and an IRR of 12–25%, which exceeds the MARR of 9.5%, indicate that converting diesel engines to B20 biodiesel is financially viable. Thus, the use of B20 biodiesel made from used cooking oil can serve as an economical, practical, and sustainable alternative energy solution for the MSME-scale tofu industry.